2017
DOI: 10.1177/1362361317717976
|View full text |Cite
|
Sign up to set email alerts
|

Technology use as a support tool by secondary students with autism

Abstract: The purpose of this study was to examine how secondary students with autism spectrum disorder use technology in supportive ways. In this self-report survey study, 472 adolescents with autism spectrum disorder enrolled in high school described the forms of technology they use and purposes for which they use it. Students reported the benefits as well as barriers to technology use at school. They reported using technology in school and home settings in a variety of supportive ways such as increasing their indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 38 publications
(45 reference statements)
3
27
0
Order By: Relevance
“…In addition, parent surveys can probe the inter-relation of technology use with parent attitudes. To date, research has largely focused on self-reporting by autistic adolescents and adults (Hedges et al 2018 ; Mazurek and Wenstrup 2013 ), though one recent exploration of parent attitudes in a modest sample revealed enthusiasm but lack of knowledge among parents (Clark et al 2015 ). It is likely that parent attitudes to technology both shape and are shaped by their child’s use of technology, as well as by external factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, parent surveys can probe the inter-relation of technology use with parent attitudes. To date, research has largely focused on self-reporting by autistic adolescents and adults (Hedges et al 2018 ; Mazurek and Wenstrup 2013 ), though one recent exploration of parent attitudes in a modest sample revealed enthusiasm but lack of knowledge among parents (Clark et al 2015 ). It is likely that parent attitudes to technology both shape and are shaped by their child’s use of technology, as well as by external factors.…”
Section: Introductionmentioning
confidence: 99%
“…Autistic people1 report high levels of use of technology—apps, software and online resources accessed through digital devices—for both leisure purposes and academic study (Hedges et al 2018; Kuo et al 2014; MacMullin et al 2016; Mazurek and Wenstrup 2013). However less is known about the use of technology by autistic people who do not find a traditional survey design accessible—such as young children or those with learning disability.…”
Section: Introductionmentioning
confidence: 99%
“…Digital technologies have been developed to support autism in areas such as social skills and social interaction (for reviews see Camargo et al, 2014 ; Grossard et al, 2017 ; Ramdoss et al, 2011 ; Schlosser & Wendt, 2008 ) and emotion recognition (for review see Berggren et al, 2018 ). Digital technology, both in school and home settings, is being used in a variety of supportive ways such as increasing autonomy, reducing anxiety and increasing social opportunities for autistic people ( Hedges et al, 2018 ), encapsulated by the term ‘digital support’. To get an idea of how profuse development in this area is, one curated database of autism apps ( http://www.appyautism.com/en/ ) lists over 400 apps for the iOS format alone.…”
mentioning
confidence: 99%
“…There is no known cause of autism and no cure for autism. However, research has shown that interventions combining with ongoing therapies can positively lead to having an independent, happy, and productive autitic person [3,4].…”
Section: Introductionmentioning
confidence: 99%